Public Satisfaction Level Towards Services at the Fire and Rescue Department of Yogyakarta - Bambang Wahono; Rinaldi Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to determine the level of public satisfaction with the services provided by the Yogyakarta City Fire and Rescue Department. This study employs a quantitative approach and utilizes surveys as the method for data collection. The population for this research consists of institutions, communities, or individuals who receive services from the Yogyakarta City Fire and Rescue Department, while the sampling technique used is purposive sampling, which involves selecting subjects based on specific criteria or objectives. The validity and reliability of the instruments were tested using SPSS software, and the data analysis technique employed was the analysis of the Public Satisfaction Index (PSI) based on the Regulation of the Minister for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. The results of this research indicate that the level of public satisfaction with the services at the Yogyakarta City Fire and Rescue Department is reflected in a Public Satisfaction Index (PSI) score of 89.30, indicating a very high quality of service.